2016
DOI: 10.1371/journal.pone.0159398
|View full text |Cite
|
Sign up to set email alerts
|

Early Phthalates Exposure in Pregnant Women Is Associated with Alteration of Thyroid Hormones

Abstract: IntroductionPrevious studies revealed that phthalate exposure could alter thyroid hormones during the last trimester of pregnancy. However, thyroid hormones are crucial for fetal development during the first trimester. We aimed to clarify the effect of phthalate exposure on thyroid hormones during early pregnancy.MethodWe recruited 97 pregnant women who were offered an amniocentesis during the early trimester from an obstetrics clinic in southern Taiwan from 2013 to 2014. After signing an informed consent form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 56 publications
1
46
1
2
Order By: Relevance
“…Of the studies that have evaluated this question, one study found positive associations with MnBP, and MBzP (Song et al 2014), while another found inverse cross-sectional associations with MEHP (Hatch et al 2008). Recent studies have investigated phthalate exposure during pregnancy as it relates with the risk of major pregnancy complications such as gestational diabetes and preterm birth (James-Todd et al 2016; Huang et al 2016; Philips et al 2016; Ferguson et al 2014; Ferguson et al 2015; Werner et al 2015). While studies have evaluated pregnancy phthalate metabolite concentrations, to our knowledge, this is among the first study to focus on maternal obesity measures as a primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that have evaluated this question, one study found positive associations with MnBP, and MBzP (Song et al 2014), while another found inverse cross-sectional associations with MEHP (Hatch et al 2008). Recent studies have investigated phthalate exposure during pregnancy as it relates with the risk of major pregnancy complications such as gestational diabetes and preterm birth (James-Todd et al 2016; Huang et al 2016; Philips et al 2016; Ferguson et al 2014; Ferguson et al 2015; Werner et al 2015). While studies have evaluated pregnancy phthalate metabolite concentrations, to our knowledge, this is among the first study to focus on maternal obesity measures as a primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies showed that rats fed DEHP through the diet displayed histopathologic alterations in the thyroid indicative of hyperactivity, increased thyroglobulin turn over, and significantly decreased plasma T 4 concentrations 13,3234 . A few epidemiological studies explored the associations of prenatal phthalates exposure with maternal thyroid function, which was assessed by metabolites concentrations in urine samples 13,16,2528 . Three studies reported that maternal phthalates exposures (e.g., MBP, MBzP, MEHP and MEHHP) were associated with reduced concentrations of TT4 13,25,28 , which were consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…A few epidemiological studies explored the associations of prenatal phthalates exposure with maternal thyroid function, which was assessed by metabolites concentrations in urine samples 13,16,2528 . Three studies reported that maternal phthalates exposures (e.g., MBP, MBzP, MEHP and MEHHP) were associated with reduced concentrations of TT4 13,25,28 , which were consistent with our results. However, Johns et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations